Der Markt fur̈ Milch - Thomas Roth; Petra Salamon (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Agricultural Markets at the Turn of 2001/2002: (4) Milk ProductionAlthough there are different trends to be seen world-wide, overall cow milk production continued to increase at a moderate rate. Import demand for dairy products remained strong in 2001 and led to relatively world high prices. With EU support prices being fixed and milk quotas raised under the Agenda 2000 the Commission tried to control the market by repeatedly adjusting subsidies for disposal of skim milk and SMP as well as on SMP and butter exports. Several member countries made changes in their sophisticated commercial quota transfer systems while the mid-term review which the Commission is committed to present in 2003 is expected to give guidance towards a later abolition of the whole EU dairy quota regime. The WTO Appellate Body Report (Canada-dairy) is, however, putting new question marks.
Keywords: 330